2019
DOI: 10.1002/chem.201901446
|View full text |Cite
|
Sign up to set email alerts
|

Direct Phenolysis Reactions of Unactivated Amides into Phenolic Esters Promoted by a Heterogeneous CeO2 Catalyst

Abstract: The direct catalytic esterification of amides that leads to the construction of C−O bonds through the cleavage of amide C−N bonds is a highly attractive strategy in organic synthesis. While aliphatic and aromatic alcohols can be readily used for the alcoholysis of activated and unactivated amides, the introduction of phenols is more challenging due to their lower nucleophilicity in the phenolysis of unactivated amides. Herein, we demonstrate that phenols can be used for the phenolysis of unactivated amides int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…The bimetallic associative mechanism might be related to heterogeneous CeO 2 system exhibited catalytic activity toward alcoholysis of N,N-dialkylamides using alcohols and phenols (eq. 15), [36,37] though it only worked at very higher temperature (175-180°C) for long reaction time (36-100 h).…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…The bimetallic associative mechanism might be related to heterogeneous CeO 2 system exhibited catalytic activity toward alcoholysis of N,N-dialkylamides using alcohols and phenols (eq. 15), [36,37] though it only worked at very higher temperature (175-180°C) for long reaction time (36-100 h).…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…[16] With respect to the catalytic transformation of tertiary amides, which are more stable than primary and secondary amides, [17] three mechanisms have been reported including oxidative addition, N,O-acyl rearrangement, and Lewis acid-assisted mechanisms. [18][19][20][21][22][23][24][25][26][27] Oxidative addition-esterification was first reported by Garg and co-workers who used nickel(0) catalysts to activate the CÀN bond of tertiary arylamides bearing functional groups such as Ph, Boc, and Ts by oxidative addition as a key step to afford the corresponding aryl esters. [18,19] Danoun and Gosmini used a low-valent cobalt catalyst system supported by 2,2'-bipyridine with metallic manganese as a reductant to catalytically activate the CÀN bond of activated arylamides bearing a Boc, Ts, or methoxycarbonyl group to give the corresponding aryl esters.…”
Section: Introductionmentioning
confidence: 99%
“…For Lewis acid-assisted esterification, FeCl 3 required stoichiometric amounts of HCl for the catalytic esterification of tertiary amides, [24] and heterogeneous cerium dioxide required a high temperature (175 8C) for the catalytic esterification of tertiary amides (Scheme 1 c). [25,26] In this context, we focused our attention on developing effective catalysts for the esterification of simple tertiary N,N-dialkyl amides. We previously found that an alkoxide-bridged manganese dinuclear complex, [(acac)(Me 2 N-Phen)Mn(m-OnBu)] 2 (2 a) (Me 2 N-Phen = 4,7-bis(dimethylamino)-1,10-phenanthroline), derived by treating an alkoxide-bridged manganese tetranuclear cubic complex [Mn(acac)(OEt)(EtOH)] 4 (1) with Me 2 N-Phen in nBuOH, was an excellent catalyst for the esterification of various N,N-dialkyl arylamides via a cooperative mechanism in which one manganese center functioned as a Lewis acid for coordinating to the amide carbonyl moiety and the second manganese center activated an alcohol to provide more nucleophilic alkoxide species (Scheme 1 d).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations